Facile synthesis of ultra-lightweight silver/reduced graphene oxide (rGO) coated carbonized-melamine foams with high electromagnetic interference shielding effectiveness and high absorption coefficient. (January 2022) - Shen, Youkang; Lin, Zhiqiang; Wei, Jianhong; Xu, Yadong; Wan, Yanjun; Zhao, Tao; Zeng, Xierong; Hu, Yougen; Sun, Rong
Abstract: Endowing electromagnetic interference (EMI) shielding foams with ultralow density and dynamic stable structure is crucial yet challenging. Here, we propose a facile one-step thermal treatment strategy to fabricate lightweight silver/reduced graphene oxide-coated carbonized melamine (CMF/rGO/Ag) hybrid foams with remarkable mechanical performance and outstanding EMI shielding effectiveness (EMI SE). Due to interfacial reinforcement of rGO between CMF skeleton and silver, the CMF/rGO/Ag foams show outstanding structural stability after 1000 cycles of a loading-unloading compression test. Moreover, The EMI SE of the foams reaches 50.6 dB at a mere density of 16 mg cm −3 . The normalized surface-specific SE is up to 7616 dB cm 2 g −1 with an ultralow Ag content of 0.09 vol%. Interestingly, the collaboration of the porous skeleton and multiple interfaces contribute to an anomalous high absorption coefficient of CMF/rGO/Ag foams (over 0.5). The high-absorption-coefficient shielding mechanism of the CMF/rGO/Ag foams was further studied by finite element analysis (FEA). The remarkable near-field EMI shielding performance of the CMF/rGO/Ag foam demonstrates that the low density and robust CMF/rGO/Ag foam have enormous advantages and wide application prospects as EMI shielding materials of electronic packaging. Graphical abstract: A silver/rGO coated carbonized melamine foam is fabricated by a one-step thermal treatment process. The as-prepared hybrid foams show excellent mechanical properties and structural stability. Due to the unique porous structure, the hybrid foams demonstrate an outstanding specific EMI SE of 7176 dB cm 2 g -1, and an extra-high absorption coefficient of 0.51 with a low Ag content of 0.09 vol%. Image 1